RFID automatic toll system / Muhammad Asyraf Aiman Rosli - Rosli, Muhammad Asyraf Aiman (2024)
This paper presents a project for the development and implementation of an RFID-Automatic toll system. The problem statement focuses on the limitations of traditional toll systems, including inefficient toll collection, high operating costs, and limited data analytics capabilities. The objectives are to design and develop an RFID automatic smart toll system that integrates seamlessly with existing toll infrastructure, and second, to evaluate the system's effectiveness in terms of accuracy, efficiency, and security. By employing Arduino uno, the report aims to streamline the toll collection process, minimize human intervention, and enable real-time data analysis for effective traffic management. The methodology of this project is use Arduino uno and put IR sensor, RFID reader and keypad as the input and LCD display, motor, and LED as the output. The project has been simulated by Proteus 8 Professional software in applying every components used and observe how it is work. As result, when user pass the IR sensor, the toll gate is close. After user scan the card at RFID reader, the toll gate will be open as user pass by the next IR sensor. Opinion on future work, the system can be integrated with other smart city initiatives, such as intelligent traffic management systems, to optimize traffic flow and reduce congestion in real-time. By automating toll collection and reducing the need for manual intervention, the system improves the overall efficiency of toll operations. This leads to reduced wait times, smoother traffic flow, and enhanced user experience for motorists